IMMU-06. PEMBROLIZUMAB AS SALVAGE TREATMENT IN CHILDREN WITH RECURRENT DIFFUSE MIDLINE GLIOMA: REPORT OF THREE CASES. Issue 2 (22nd June 2018) - Lee, Yi-Yen; Chen, Hsin-Hung; Chen, Yi-Wei; Chang, Feng-Chi; Lin, Shih-Chieh; Liang, Muh-Lii
Abstract: Diffuse midline glioma including diffuse intrinsic pontine glioma is a high grade, infiltrative and very poor prognosis primary pediatric brain tumor, which constitutes 20% within children population. Only radiation therapy was considered a standard treatment until now. Recently, immune checkpoint inhibitor brought us hope as treatment for advanced solid tumor, such as metastasis melanoma. There was only one published report for Pembolizumab, a monoclonal antibody against programmed death-1(PD-1), used in primary brain tumor which showed ineffective results. Other trials related to Pembrolizumab use in glioblastoma are still undergoing. In our institution, there were three children treated with Pembrolizumab after recurrent of diffuse midline glioma, and we collected medical records from these patients to summarize treatment results, complications, and comparison with previous study. The median overall survival from using of Pembrolizumab was 2.47 months. Numbers of cycle of Pembrolizumab were between 1-4 in these patients. One of these children developed moderate hypersensitivity pneumonitis which suspected as adverse effect of Pembrolizumab. All children developed disease progression and no benefits of survival were observed. Because of our number of case was limited, the effectiveness of Pembrolizumab still need more trials and selecting appropriate patients is important in clinical practice.